The Role of Islamic Rural Bank in Financing the SMEs: Customer Perspective Analysis (Case Study of Amanah Ummah Bank in Bogor City, Indonesia) - Irfan Syauqi Beik; Qurroh 'Ayyuniyyah; Laily Dwi Arsyanti (Tazkia Islamic Finance and Business Review, 2009)
One of the basic problems faced by small scale and medium enterprises (SMEs) in Indonesia is the availability of financing access provided by financial institutions including banking institution. There are three types of Islamic bank operating in Indonesia presently: Islamic commercial bank, Islamic banking unit and Islamic rural bank. Providing the SMEs with sufficient financing source is highly required. This paper attempts to observe empirically the role that have been played by Islamic rural bank in financing the SMEs, by taking case study of Amanah Ummah Bank, the best Islamic rural bank in the country. Thirty small and medium entrepreneurs have been selected as the sample of the research, and have been deeply interviewed on September and October 2008. Descriptive statistics, IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index) methods have been used as analytical methods. The results show that the financing given by the bank does really help the SMEs. There are three factors, which are important, and which have satisfied the SMEs. These are easiness of bank’s requirements, the speed of financing approval, and bank’s services. In general, the respondents are of the view that the bank has shown a good performance.Keywords : SMEs, Islamic rural bank, customers’ perception